A Metaheuristic Approach for Encrypting Blockchain Data Attributes Using Ciphertext Policy Technique. (10th February 2022) - Deb, Nabamita; Elashiri, Mohamed A.; Veeramakali, T.; Rahmani, Abdul Wahab; Degadwala, Sheshang
Abstract : Unlike public chains, the Alliance Blockchain Hyperledger Fabric has a member management service mechanism that may provide data isolation security at the channel level. However, because this data isolation security technique synchronizes plaintext data inside the channel, data leakage is still a possibility. Furthermore, in some fine-grained privacy protection circumstances, channel-based data access restriction is ineffective. In order to solve the data privacy security problems in the above-mentioned consortium chain superledger, a blockchain data attribute encryption scheme based on ciphertext policy is proposed. Combining the original Fabric Certificate Authority module in the Hyperledger, the proposed scheme can realize the user-level fine-grained security access to control blockchain data while also realizing the secure distribution of user attribute keys in the blockchain data attribute encryption scheme based on the ciphertext policy scheme. The security analysis of the scheme shows that the scheme achieves the security goals of attribute-based encryption user attribute private key secure distribution and data privacy protection. The scope of this research is that this study confirms that the solution's architecture achieves fine-grained access control of private data on the Hyperledger Blockchain network and also the security objectives of secure transmission of user characteristic secret keys and data privacy protection. The performance analysis part also shows that the proposed scheme has good usability.